Sintesis Nanopartikel Ekstrak Kulit Batang Tanaman Kayu Jawa (Lannea Coromandelica) Tersalut Kitosan - Hartati; Fitratul Insaniah Rusli; Andi Mu'nisa; Halifah Pagarra (Jurusan Biologi Universitas Negeri Makassar, 2022)
This study aims to synthesize nanoparticles of Javanese bark extract (Lannea coromandelica) coated with chitosan and characterization of the synthesis results. The extraction of Javanese bark (Lannea coromandelica) was carried out by the maceration method using a 70% ethanol solvent. The bark extract of the Javanese wood plant (Lannea coromandelica) was synthesized to form chitosan-coated nanoparticles using the ionic glassing method and the synthesis results were characterized using X-Ray Difraction (XRD). The results showed that the synthesis of nanoparticles of the bark extract of the Javanese wood plant (Lannea coromandelica) coated in chitosan has a nanoparticle size of 24.9 nm.